Kinetics of Reactive Extraction of Nd from Nd2O3 with TBP-HNO3 Complex in Supercritical Carbon Dioxide - 朱礼洋 段五华 徐景明 朱永[贝睿] (Chinese journal of chemical engineering, 2009)
The process based on supercritical fluid extraction for reprocessing of the spent nuclear fuel has some remarkable advantages over the plutonium-uranium extraction （PUREX） process. Especially, it can minimize the generation of secondary waste. Dynamic reactive extraction of neodymium oxide （Nd2O3） in supercritical carbon dioxide （SC-CO2） containing tri-n-butyl phosphate-nitric acid （TBP-HNO3） complex was investigated. Temperature showed a positive effect on the extraction efficiency, while pressure showed a negative effect when the unsaturated TBP-HNO3 complex was employed for the dynamic reactive extraction of Nd2O3 in SC-CO2. Both temperature and pressure effects indicated that the kinetic process of the reactive extraction was controlled by the chemical reaction. A kinetic model was proposed to describe the extraction process.